Review of Experimental Investigations on Wells Turbines for Wave Energy Conversion - Fabio Licheri; Tiziano Ghisu; Francesco Cambuli; Pierpaolo Puddu; Mario Carta (Energies, 2025)
Wells turbines are one of the most attractive types of rotating machines installed in Oscillating Water Column (OWC) devices, owing to their simplicity of construction and reliability. Their unconventional design, with symmetrical blades staggered orthogonally with respect to the axis of rotation, simultaneously represents one of the main strengths and weaknesses of the turbine, and makes their aerodynamic behavior complex and significantly different from that of other types of machines. The importance of numerical analyses in explaining the physics behind the Wells rotor operation has significantly grown in recent years as proved by the vast available literature. Nevertheless, experimental analyses still hold an important role in modern turbomachinery design, both for the validation of Computational Fluid Dynamics (CFD) models and for verifying the improvements suggested by optimized design in a realistic environment. This review aims to collect and classify published experimental studies on Wells turbines, distinguishing among the types of experimental setups, methodologies adopted, and measurements performed, to identify the current research gaps and guide future experimental research.